Tissue eosinophilia in oral intraepithelial neoplasia as a probable indicator of invasion - Martinelli-Kläy, C. P.; Lombardi, T.; Mendis, B. R. R. N.; Soares, E. G.; Salvado, F.; Courvoisier, D. S.; Maurício, Paulo (John Wiley and Sons, 2018)
Objective: to investigate the presence of eosinophils in oral intraepithelial neoplasia (OIN) and oral squamous cell carcinoma (OSCC) lesions and its relation to invasion.

Subjects and methods: ninety‐nine oral biopsies were selected and subdivided into the following: OIN‐1(16 cases), OIN‐2 (18 cases), OIN‐3 (17 cases), microinvasive OSCC (10 cases), non‐metastatic OSCC (22 cases) and metastatic OSCC (16 cases). The tissue eosinophilia was evaluated histologically in slices stained with haematoxylin and eosin.

Results: Eosinophil distribution was associated with diagnosis severity (p < .01). A significant difference was found between OIN‐3 or microinvasive OSCC and non‐metastatic or metastatic OSCC. Stromal invasion threshold was 7 eos/10 high power field (hpf) (96.1% specificity and 62.5% sensitivity). Eosinophils were absent in OIN‐1; in OIN‐2, two cases were positive. In OIN‐3, five cases showed tissue eosinophilia, four of which had ≥3 eos/hpf or ≥7 eos/10 hpf. Three cases were suspected of invasion; two had a previous history of OSCC with elevated eosinophil infiltrate. In microinvasive OSCC, the four positive cases presented ≥3 eos/hpf and ≥7 eos/10 hpf. Although not significantly different, non‐metastatic invasive OSCC had a higher number of cases (68.2%) with ≥22 eos/10 hpf contrasting with 50% in metastatic OSCC.

Conclusion: our results suggest that eosinophils can be considered an indicator of invasion in OIN, helping in cases of difficult diagnosis.
Keywords: Oral epithelial dysplasia; Oral intraepithelial neoplasia; Oral squamous cell carcinoma; Tissue eosinophilia